Diffuse alveolar haemorrhage – Is it an unusual or unlooked presentation of Fat Embolism Syndrome? A Case report and review of literature - Maskey, Dipesh (Journal of Advances in Internal Medicine, 2020)
Fat embolism syndrome (FES) is a constellation of clinical symptoms characterized by a triad of respiratory insufficiency, altered sensorium and petechiae occurring after orthopaedic trauma or following surgical manipulation of long bones and spine. The diagnosis is based on clinical presentation and excluding other possible conditions. Beside histopathology, none of the investigations such as fat macroglobinuria in urine or lipid laden macrophages in bronchoalveolar lavage (BAL) is 100% specific. At times FES can present with atypical presentation such as intra alveolar haemorrhage and only high index of suspicion can help in making diagnosis.